Urban vs Suburban: Is the Door-to-Balloon Time Affected by Geographic, Socioeconomic, or Racial Differences? A Tale of Two Campuses. (8th September 2020) - Zughaib, Marc; Ters, Patrick; Singh, Robby; Zughaib, Marcel
Abstract : Background . In 2004, the ACC/AHA released guidelines in the treatment of ST-segment elevation myocardial infarction (STEMI) within a time window from the time a patient physically enters the hospital to the time of percutaneous coronary intervention (PCI). This time window is defined as the door-to-balloon time (DTB) and is recommended to be under 90 minutes to improve patient mortality. To add another layer of complexity, patients with varying socioeconomic status and racial differences experience large disparities in health. Our institution provides care for patients in two locations separated by approximately 30 miles within the Detroit metropolitan area. We aimed this study to investigate any differences between DTB times of our two campuses (urban versus suburban population) as well as any differences in the components that comprise DTB times. Methods . We retrospectively collected data on all patients who presented to either Campus 1 or Campus 2 with a STEMI from 2016 to 17. DTB times, demographical, temporal, and anatomical data were collected and analyzed. Our search included 169 patients who met the full inclusion criteria. Results . The combined average of the overall DTB time for both campuses was 81 minutes, 15 seconds (95% CI: 78:05, 84:25). The average DTB time in Campus 1 was 78 minutes and 41 seconds (95% CI: 73:05, 84:18) versus 82 minutes and 46 seconds (95% CI: 78:55, 86:38) for Campus 2 (p = 0.24 ). There were no statistically significant differences between either campuses within the separate metrics that comprise DTB times. Conclusions . Our study demonstrated that we have been able to provide high-quality care to all of our patients presenting with STEMI at either campus, regardless of socioeconomic differences in the populations they serve. Additionally, each campus has demonstrated DTB well below the nationally recommended guidelines.